Implementation Of Character Education For Students At Vocational School Of Daruttaqwa Gresik - Ammar Bueraheng; Ode Mohamad Man Arfa Ladamay; Muya sarah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Noble moral education has so far emphasized the knowledge aspect rather than the attitude and application aspects. The phenomenon of student brawls and promiscuity is evidence. Public schools with their distinctive curriculum are considered successful in managing moral character education. However, not all schools are able to manage it effectively. This study aims to find out and explore data about how to plan, implement, evaluate, and educate morals. Research using a qualitative approach, is a case study of SMK DARUTTAQWA GRESIK. The findings of the study show that schools carry out program planning starting with the determination of the vision and mission, objectives, graduation standards, compiling an integrated curriculum integrating the national curriculum and the typical religious curriculum with an emphasis on moral education. evaluation is carried out continuously on all aspects of student activities. Success is marked by changes in student behavior such as discipline, diligent worship, obedience, honesty, and achievement. The community has more trust and institutions are growing. One of the research recommendations is that all stakeholders commit to the plan, set an example and provide continuous coaching and forge partnerships.